Agriculture and sustainable communities: Reflections from a comparative case study. Issue 1 (1st January 2018) - Suh, Jungho
Abstract: The ecovillage movement places emphasis on the holistic sustainability of living. This study undertakes a comparative analysis of two forms of ecovillage development: establishing new intentional communities and retrofitting existing traditional villages. This article describes the achievements and limitations of intentional communities, with a special reference to the Findhorn Ecovillage in Scotland, Crystal Waters in Australia, and Ecovillage at Ithaca (EVI) in the US. For comparison purposes, this article introduces Mundang Ecovillage, a traditional village located in South Korea. The three intentional communities have given priority to building low-impact housing and relying on renewable energy sources. Mundang Ecovillage has strengths in the aspects of agricultural sustainability and social cohesion. This study posits that collective and cooperative communal work on organic farms generates social interactions and enhances integrity among community members. Thus, a great deal of synergy can be generated from the co-development of traditional and intentional communities.